Chapter Ecological status of the Tuscan Archipelago rocky habitats assessed by the MedSens index - Turicchia, Eva (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
MedSens index provides the environmental status of subtidal rocky coastal habitats based on open data collected by trained volunteers using the Reef Check Mediterranean Underwater Coastal Environment Monitoring protocol. It is based on 25 species, incorporating their sensitivities to the EU Marine Strategy Framework Directive pressures and their distributions and abundances. MedSens was applied along the Tuscan Archipelago National Park Islands' coasts, providing the mean sensitivity of the assemblages. It can help decision-makers in implementing marine biodiversity conservation measures.